Communicating culinary desire: persuasive strategies in Netflix's 'Flavoured Origins' - Henricus Hans Setyawan Prabowo; Md. Anisul Haque; Misbah Ul Islam (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Food documentaries have become influential tools for cultural representation on streaming platforms, yet little is known about how they construct culinary authenticity and engage viewers psychologically. This paper examines how Netflix's Flavorful Origins uses persuasive visual strategies to communicate culinary desire while representing regional Chinese cuisines. Three episodes ("Mutton," "Noodles," and "Potato") were analyzed using Bordwell and Thompson's continuity editing framework and Barthesian visual semiotics to identify patterns in cinematography and narrative sequencing. The analysis reveals three key persuasive mechanisms: geographic anchoring (establishing cultural authenticity through location), sensory choreography (using close-up shots to stimulate embodied responses), and temporal scripting (sequencing traditions within modern narratives). Results show that 78% of frames emphasize material close-ups, creating a visual syntax that fetishizes ingredients while activating viewers' sensory engagement. However, a tension emerges between the series's claims to traditional authenticity and its use of commercial food-media aesthetics, including hyper-color grading and standardized editing patterns. The paper argues that Flavorful Origins practices "culinary nationalism" by packaging regional cuisines as both ethnographically authentic and globally consumable. This study contributes to food media studies by demonstrating how streaming platforms use continuity editing as psychological persuasion, transforming cultural documentation into desire cultivation and revealing the commodification of authenticity in digital gastronomy.